(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper is based on the investigation conducted to study the level of Computer Phobia among Secondary School Teachers within Aizawl City. The sample consisted of 200 secondary school students. Computer Phobia was measured by “Computer Phobia Scale” developed by Dr. S. Rajasekar and Dr. P. Vaiyapuri Raja. Mean, Standard Deviation and ‘t’ test was used for analysing the data. There is significant difference between Computer Attitude of male and female higher secondary school students. The result revealed that there is a significant difference in the level of Computer Phobia between different age groups of Secondary School Teachers. It also revealed that there is no significant difference in the level of Computer Phobia between Secondary School Teachers with B.Ed. degree and without B.Ed. degree, between married and unmarried and between Secondary School Teachers coming from joint family and nuclear family.